Insight into the knowledge, attitude and practices of hand hygiene with alcohol based hand rubs in a public sector tertiary care hospital of a developing country - Balkhi, Fizra; Nasir, Aamna; Asghar, Ayesha; Patel, Farhan; Zafar, Marium; Nasir, Anum (International Journal Of Community Medicine And Public Health, 2021)
Background: Health care worker’s hands are mostly responsible for transmission of healthcare associated infections (HCAI). In such instances, alcohol based hand rubs have been endorsed by WHO as the gold standard for hand hygiene for visibly clean hands; whereas, for visibly dirty hands soap and water is recommended. In developing countries (like Pakistan), affected people frequently exceed 25%. However, limited infrastructure in these countries hinders the performance of hand hygiene, but the use of alcohol-based hand rubs in such adverse situations is a practical solution to these constraints. Methods: In January 2021, we initiated a 12 week cross-sectional study in a public sector tertiary care hospital of Karachi, Pakistan. All participants were given a self-designed questionnaire with a consent form thereby giving us permission to use the data. Data was analyzed using statistical package for the social sciences (SPSS version 23). Results: 84.3% of the participants had received prior instructions on hand hygiene; however 71.7% respondents did not have access to alcohol based hand rubs. When questioned if they followed WHO’s five moments of hand hygiene, only 50.5% use alcohol based hand rubs before patient contact; 88.6% used it after patient contact; 83.2% after body fluid exposure risk; 77% before an aseptic task and 78.6% after contact with patient’s surroundings. Conclusions: There is a dire need for concerned authorities to enforce proper hand hygiene in public hospitals of developing countries in order to curb health care associated infections and prolonged hospital stays.